Merthyr politics: the making of a working-class tradition. Four lectures [by] G.A. Williams, I.G. Jones, K.O. Morgan [and] J.w. England, originally delivered to the Merhyr branch of the W.e.A. [...], 1964-5. Ed, with a forew., by G. Williams (University of Wales Press, 1966)
With ills and index.